Primary Succession of Nitrogen Cycling Microbial Communities Along the Deglaciated Forelands of Tianshan Mountain, China - Zeng, Jun; Lou, Kai; Zhang, Cui-Jing; Wang, Jun-Tao; Hu, Hang-Wei; Shen, Ju-Pei; Zhang, Li-Mei; Han, Li-Li; Zhang, Tao; Lin, Qin; Chalk, Phillip M.; He, Ji-Zheng (Frontiers in Microbiology, 2016)
Structural succession and its driving factors for nitrogen (N) cycling microbial communities during the early stages of soil development (0 to 44 years) were studied along a chronosequence in the glacial forelands of the Tianshan Mountain No.1 glacier in the arid and semi-arid region of central Asia. We assessed the abundance and population of functional genes affiliated with N-fixation (nifH), nitrification (bacterial and archaeal amoA), and denitrification (nirK/S and nosZ) in a glacier foreland using molecular methods. The abundance of functional genes significantly increased with soil development. N cycling community compositions were also significantly shifted within 44 years and were structured by successional age. Cyanobacterial nifH gene sequences were the most dominant N fixing bacteria and its relative abundance increased from 56.8% to 93.2% along the chronosequence. Ammonia-oxidizing communities shifted from the Nitrososphaera cluster (AOA-amoA) and the Nitrosospira cluster ME (AOB-aomA) in younger soils (0 year and 5 years) to communities dominated by soil and sediment 1 (AOA-amoA) and Nitrosospira Cluster 2 Related (AOB-aomA) in older soils (≥17 years). Most of the denitrifers closest relatives were potential aerobic denitrifying bacteria, and some other types of denitrifying bacteria (like autotrophic nitrate-reducing, sulfide-oxidizing bacteria and denitrifying phosphorus removing bacteria) were also detected in all soil samples. The regression analysis showed that N cycling microbial communities were dominant in younger soils (0 year to 5 years) and significantly correlated with soil total carbon, while communities that were most abundant in older soils were significantly correlated with soil total nitrogen. These results suggested that the shift of soil C and N contents during the glacial retreat significantly influenced the abundance, composition and diversity of N cycling microbial communities.